Interseismic coupling, stress evolution, and earthquake slip on the Sunda megathrust. Issue 16 (20th August 2013) - Nalbant, Suleyman; McCloskey, John; Steacy, Sandy; NicBhloscaidh, Mairead; Murphy, Shane
<x xml:space="preserve">Abstract</x> [1] The extent to which interseismic coupling controls the slip distribution of large megathrust earthquakes is unclear, with some authors proposing that it is the primary control and others suggesting that stress changes from previous earthquakes are of first‐order importance. Here, we develop a detailed stress history of the Sunda megathrust, modified by coupling, and compare the correlation between slip and stress with that of slip versus coupling. We find that the slip distributions of recent earthquakes are more consistent with the stress field than with the coupling distributions but observe that in places, the stress pattern is strongly dependent on poorly constrained values of slip in historical earthquakes. We also find that of the 13 earthquakes in our study for which we have hypocentral locations, only two appear to have nucleated in areas of negative stress, and these locations correspond to large uncertainties in the slip distribution of pre‐instrumental events.